The analysis of the Lithuanian teacher’s databases in the scope of mathematics’ teaching - Dzemyda, Gintautas; Kurasova, Olga; Šaltenis, Vydūnas; Tiešis, Vytautas (Lietuvos matematikos rinkinys, 2001)
In the paper we present the results of integrated analysis of data stored in the system of the Lithuanian teacher’s database and of data from other sources representing the state of education system and the demographical changes in Lithuania. The research covers the analysis of dynamics of pedagogical staff and pupils, and the prognosis of tendency that have impact on the development of information society. Special emphasis is placed on teachers of mathematics.